Who Cares in Nicaragua? A Care Regime in an Exclusionary Social Policy Context - Martínez Franzoni, Juliana (2011)
In Latin American countries with historically strong social policy regimes (such as those in the Southern Cone), neoliberal policies are usually blamed for the increased burden of female unpaid work. However, studying the Nicaraguan care regime in two clearly defined periods — the Sandinista and the neoliberal eras — suggests that this argument may not hold in the case of countries with highly familialist social policy regimes. Despite major economic, political and policy shifts, the role of female unpaid work, both within the family and in the community, remains persistent and pivotal, and was significant long before the onset of neoliberal policies. Nicaragua's care regime has been highly dependent on the ‘community’ or ‘voluntary’ work of mostly women. This has also been, and continues to be, vital for the viability of many public social programmes.